Beyond the second-order magnetic anisotropy tensor: higher-order components due to oriented magnetite exsolutions in pyroxenes, and implications for palaeomagnetic and structural interpretations. Issue 2 (25th July 2020) - Biedermann, Andrea R; Jackson, Mike; Chadima, Martin; Hirt, Ann M; Feinberg, Joshua M
SUMMARY: Exsolved iron oxides in silicate minerals can be nearly ideal palaeomagnetic recorders, due to their single-domain-like behaviour and the protection from chemical alteration by their surrounding silicate host. Because their geometry is crystallographically controlled by the host silicate, these exsolutions possess a shape preferred orientation that is ultimately controlled by the mineral fabric of the silicates. This leads to potentially significant anisotropic acquisition of remanence, which necessitates correction to make accurate interpretations in palaeodirectional and palaeointensity studies. Here, we investigate the magnetic shape anisotropy carried by magnetite exsolutions in pyroxene single crystals, and in pyroxene-bearing rocks based on torque measurements and rotational hysteresis data. Image analysis is used to characterize the orientation distribution of oxides, from which the observed anisotropy can be modelled. Both the high-field torque signal and corresponding models contain components of higher order, which cannot be accurately described by second-order tensors usually used to describe magnetic fabrics. Conversely, low-field anisotropy data do not show this complexity and can be adequately described with second-order tensors. Hence, magnetic anisotropy of silicate-hosted exsolutions is field-dependent and this should be taken into account when interpreting isolated ferromagnetic fabrics, and in anisotropy corrections.